Internet addiction among Faculty of Computer and Mathematical Sciences Students in UiTM Seremban 3 / Fatin Nadiah Nazaruddin, Nur Athirah Mohd Salleh and Siti Nurain Berahim@Ibrahim - Nazaruddin, Fatin Nadiah; Mohd Salleh, Nur Athirah; Berahim@Ibrahim, Siti Nurain (2019)
This is a comprehensive study on Internet addiction among students of Faculty of Computer and Mathematical Sciences in UITM Seremban 3, Negeri Sembilan. The research was done to explore the prevalence of internet addiction and the significant factors that contribute to it. As the researchers are studying in UITM Seremban 3, it is convenient to use UITM Seremban 3 students as their sample. 306 respondents from different programme of FSKM were taken to complete this research. The method used in this research is descriptive and logistic regression, which then will be analyzed by using SPSS. It is found that 189 respondents were addictive. The findings revealed that those students who have highly chance to be addicted were from age between 19 - 22, male gender and programme study CS 112, CS 241, CS 247 and CS 248. Awareness on Internet addiction and their bad impact towards future life should be spreading to everyone or surroundings so, the addicted person can manage to have a good and better lifestyle.